Genome-wide association study of patients with atrioventricular nodal reentry tachycardia. (25th November 2020) - Andreasen, L; Ahlberg, G; Hartmann, J; Paludan-Mueller, C; Jensen, H.K; Riahi, S; Hansen, J; Sandgaard, N; Haunsoe, S; Kanters, J.K; Ellervik, C; Bundgaard, H; et al.
Abstract: Background: Supraventricular tachycardias (SVTs) originate from the atria or the area close to the AV node. AV nodal reentry tachycardia (AVNRT) is one of the tachyarrhytmias comprising the group of SVTs. The typical patient is female, young at disease onset, with a structurally normal heart. At present we do not know the etiology of AVNRT. We therefore hypothesized that AVNRT might be caused by changes in the DNA. Methods: DNA from purified blood was obtained from patients with AVNRT verified by an invasive electrophysiological study. Patients were recruited from five ablation centers in Denmark and individuals from the general population of Denmark (the BEFUS cohort) served as controls. DNA was subjected to chip genotyping, imputation and analyses in a genome-wide association study (GWAS) setup. Results: A GWAS on 1, 143 AVNRT patients and 3, 004 controls revealed one locus close to the gene MYH6 to reach genome-wide significance for association with AVNRT (P=4.8x10 –8 ). MYH6 encodes the α-isoform of the protein myosin heavy chain important for the contractile units of the heart, the sarcomeres. The gene is predominantly expressed in the atria. Additional subthreshold loci located close to other plausible arrhythmia genes were identified. Conclusion: We report the first genetic locus to be associated with AVNRT close to the sarcomere gene MYH6. This is, to our knowledge, the first gene ever associated with AVNRT. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): Rigshospitalets Forskningspulje - 3 years PhD salary